Budaya Kula Pahari sebagai Media Pendidikan dalam Membangun Kerukunan Masyarakat Dayak di Kalimantan Tengah - Hamdanah Hamdanah; Muhammad Fikri Firdausi; Miftahurrizqi Miftahurrizqi; Miftahussa'adah Miftahussa'adah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Central Kalimantan is one of the places that is very heterogeneous both in terms of ethnicity and religion, so related to harmony needs to be maintained so that life becomes peaceful and peaceful. This paper outlines issues related to community harmony in Central Kalimantan through Islamic spirit and local wisdom. This research uses a qualitative type with a library research approach. The result of the discussion: Unharmony still arises due to several factors, such as narrow religious understanding, political and economic disparities, competition between indigenous and migrant populations, and differences in socio-cultural values that can trigger conflict. The concept of Ukhuwah in the Qur'an includes: Ukhuwah Islamiyyah (brotherhood based on religion), Ukhuwah basyariyyah (brotherhood among humans), and Ukhuwah wathaniyyah (brotherhood based on nation). Kula Pahari is a Dayak local wisdom concept that emphasizes brotherhood and family values, intertwined in the Huma Betang culture. Inter-religious harmony in Central Kalimantan needs to be fostered through recognition of local wisdom that is in line with religious principles. The concept of Kula Pahari shows that people can live in harmony despite differences, by maintaining manners and spiritual morals that prioritize kinship and brotherhood. The demographic diversity in Central Kalimantan is an important asset for building religious harmony. By integrating the values of Ukhuwah and local wisdom, the people of Central Kalimantan can live in harmony.